2020
DOI: 10.3390/s20143820
|View full text |Cite
|
Sign up to set email alerts
|

Recent Analysis of Forged Request Headers Constituted by HTTP DDoS

Abstract: Application Layer Distributed Denial of Service (DDoS) attacks are very challenging to detect. The shortfall at the application layer allows formation of HTTP DDoS as the request headers are not compulsory to be attached in an HTTP request. Furthermore, the header is editable, thus providing an attacker with the advantage to execute HTTP DDoS as it contains almost similar request header that can emulate a genuine client request. To the best of the authors’ knowledge, there are no recent studies that pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…It is also because the request header is not mandatory to be given, which allowed network intruders to generate the forged headers as legitimate HTTP requests. Jaafar et al [13] also demonstrated this weaknesses by using used eight different types of attacks in which the results showed that, there are similarities and differences in the fake request headers in both internal and external networks, thus, this can make HTTP requests appear authentic when launching HTTP DDoS attacks. In fact, it was highlighted that the request header needs a major improvement in terms of security to prevent the request header from being easily manipulated by malicious attackers.…”
Section: Review Of Existing Ddos Attack On Http/2mentioning
confidence: 99%
“…It is also because the request header is not mandatory to be given, which allowed network intruders to generate the forged headers as legitimate HTTP requests. Jaafar et al [13] also demonstrated this weaknesses by using used eight different types of attacks in which the results showed that, there are similarities and differences in the fake request headers in both internal and external networks, thus, this can make HTTP requests appear authentic when launching HTTP DDoS attacks. In fact, it was highlighted that the request header needs a major improvement in terms of security to prevent the request header from being easily manipulated by malicious attackers.…”
Section: Review Of Existing Ddos Attack On Http/2mentioning
confidence: 99%
“…The detection of DDoS attacks is very challenging [ 2 ]. DDoS attacks are kind of cyber-attack that target a specific machine or server and lead them to stop providing their services to the devices that are connected to this machine.…”
Section: Introductionmentioning
confidence: 99%